THE EFFECT OF PARTIAL DICTATION AS INSTRUCTIONAL DEVICE ON STUDENTS' LISTENING COMPREHENSION AT SECOND SEMESTER STUDENTS OF UNIVERSITAS MUHAMMADIYAH KENDARI - Jenny Samosir; Tambunan Tambunan; Ader laepe (Halu Oleo University, 2020)
This research reports the effect of Partial Dictation as instructional device on students’ listening comprehension at second semester students of Universitas Muhammadiyah Kendari academic year 2019/2020. It was then implemented in Basic - level listening class with 25 participants. Design of the research was quantitative which applied quasy experimental design. The samples were taken through purposive sampling consisted of 50 pArticipants. Two groups participated in this research, i,e one experimental group and control group. A diagnostic test on listening was administered to the both groups. Over 5 meetings, Control Group taught by non partial dictation exercises or conventionally while Experiment Group received Partial Dictation exercises. A post-test was given to the both groups after 5 meetings. In addition to the post-test, Experiment Group worked out with 5-Likert Scale adopted questionnaires to assess their motivation toward Partial Dictation as supporting data. The results of Independent t-test showed the level of significant is .000, p < 0.05. Furthermore, it explained that Ha was accepted, so that it can be concluded that teaching listening comprehension through Partial Dictation as instructional device has significant effect than teaching listening comprehension by non partial dictation. Meanwhile, motivation questionnaires revealed that 62 % of the participants were in moderate category to learn through partial dictation technique in facilitating their listening.Keywords:Listening Comprehension, partial dictation, listening motivation